EPR Relaxation‐Enhancement‐Based Distance Measurements on Orthogonally Spin‐Labeled T4‐Lysozyme. Issue 14 (14th June 2013) - Razzaghi, Sahand; Brooks, Evan K.; Bordignon, Enrica; Hubbell, Wayne L.; Yulikov, Maxim; Jeschke, Gunnar
Abstract Lanthanide‐induced enhancement of the longitudinal relaxation of nitroxide radicals in combination with orthogonal site‐directed spin labeling is presented as a systematic distance measurement method intended for studies of bio‐macromolecules and bio‐macromolecular complexes. The approach is tested on a water‐soluble protein (T4‐lysozyme) for two different commercially available lanthanide labels, and complemented by previously reported data on a membrane‐inserted polypeptide. Single temperature measurements are shown to be sufficient for reliable distance determination, with an upper measurable distance limit of about 5–6 nm. The extracted averaged distances represent the closest approach in LnIII–nitroxide distance distributions. Studies of conformational changes and of bio‐macromolecule association‐dissociation are proposed as possible application area of the relaxation‐enhancement‐based distance measurements.